A Conceptual Framework of Eco-Blended Learning Based on Ecological Systems Theory for Indonesian Language Instruction in Higher Education - Ratih Utami Ramadhaniati; Ervan Johan Wicaksana; Eddy Haryanto; Saharudin; Hadiyanto (Scidac Plus, 2026)
Indonesian language learning in higher education faces increasingly complex challenges, including low student engagement, limited integration of digital technology, and the need for instructional designs that respond to the demands of 21st-century learning. Although blended learning has been widely implemented, its application has often focused primarily on technological delivery rather than on the broader ecological context that shapes the learning process. This article aims to propose a conceptual framework of Eco-Blended Learning by integrating blended learning principles with Bronfenbrenner’s Ecological Systems Theory. This study employed a conceptual review design through thematic literature synthesis of studies on blended learning, ecological systems theory, higher education, Indonesian language learning, and emerging digital technologies in education. The analysis focused on identifying conceptual relationships among these domains and mapping the five ecological systems microsystem, mesosystem, exosystem, macrosystem, and chronosystem onto relevant components of blended learning design. The findings indicate that the integration of ecological systems theory into blended learning can generate a learning model that is more holistic, contextual, flexible, and adaptive. The proposed framework positions students at the center of the learning process within an ecosystem shaped by direct interaction, inter-environmental relationships, institutional support, educational culture, and temporal change. Therefore, Eco-Blended Learning is expected to provide both a theoretical contribution to blended learning scholarship and a practical foundation for designing Indonesian language instruction in higher education.